THE DETERMINANTS OF EMPLOYEE INTEREST TO COMMIT WHISTLEBLOWING - Alfian Setyo Poespito (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This research aims at predicting and explaining the effects of attitude, subjective norm, perceiced behavioral control, organizational commitment, personal cost, and the seriousness level of fraud on the interest of commit whistleblowing. The objects of the study are financial staffs of the faculty and university levels at the University of Brawijaya. The data are collected through survey toward 96 respondents and analyzed using partial least square technique by means of SmartPLS software. The result of the analysis shows that perceived behavioral control and the seriousness level of fraud influence the interest to whistleblowing. Meanwhile, attitude, subjective norm, organizational commitment, and personal cost do not affect such an interest. The implication of this research is relevant for state universities to consider perceived behavioral control and the seriousness level of fraud in applying and developing a whistleblowing system.Keyword: perceived behavioral control, the seriousness level of fraud.